Trichoderma: a multifunctional agent in plant health and microbiome interactions - Paulina Guzmán-Guzmán; Hassan Etesami; Gustavo Santoyo (BMC Microbiology)
Abstract The beneficial fungus Trichoderma is a key component of agricultural soils, contributing to sustainable crop production through multiple mechanisms. Among its major roles are the suppression of plant pathogens, promotion of plant growth, and activation of plant immune responses. This study reviews recent advances in understanding the modes of action of Trichoderma spp. related to pathogen control and plant growth promotion, using comparative analysis of its interactions across different plant-associated habitats. In recent years, considerable progress has been made in elucidating how Trichoderma interacts with plants in the rhizosphere, endosphere, and phyllosphere, where it exhibits distinct colonization patterns and functional traits. Additionally, this review explores emerging but less-studied topics, such as the involvement of Trichoderma in the pathobiome concept. Finally, we discuss the synergistic interactions between Trichoderma and other plant-associated microorganisms, highlighting their importance in shaping complex microbial networks within agroecosystems.